The role of path dependency and managerial intentionality: a perspective on international business research - Hutzschenreuter, Thomas; Pedersen, Torben; Volberda, Henk W (Journal of International Business Studies, 2007)
Several decades of research in the field of international business have advanced various theories and studies on the internationalization of firms. Our assessment of the literature on internationalization shows that the focus has been primarily on path-dependency and learning-based aspects of internationalization, while managerial intentionality and the possibility of managers making deliberate strategic choices towards further internationalization have not been very prominent in the IB literature. We argue that internationalization paths and processes should be approached as a joint outcome of management intentionality and experience-based learning. In other words, managers are assumed to have the ability and the intention to influence the evolutionary paths of the firm. We derive a future research agenda that calls for the pursuit of this promising and emergent research stream. Moreover, we develop a model integrating managerial intentionality, knowledge/experience and other factors (institutional and selection forces) to explain heterogeneous outcomes of internationalization positions, paths and processes.